Capital structure determinants of Portuguese footwear sector SMEs: Empirical evidence using a panel data. - Pacheco, Luís Miguel (2016)
The main objective of this paper is to study the capital structure determinants of SMEs in the footwear industry and their indebtedness. Using panel data methodology and considering a sample of 70 firms we study the capital structure determinants between 2010 and 2013. The paper examines the indebtedness level in light of the two main theories – the Trade-off theory and the Pecking Order theory and we chose the footwear sector because of its importance in the Portuguese economy. In addition to total indebtedness we extend the literature by analyzing the differences between short-term and long-term indebtedness and the impact of the presence in foreign markets on debt structure. The results suggest that profitability, growth, total liquidity, risk and presence in foreign markets are key factors affecting the capital structure of footwear firms and that Pecking Order theory seems more suited to those firms.